Characterization of InP SC QD LD After Am-Be Neutron Irradiation - rajkhan, abdulmalek (Journal of King Abdulaziz University: Engineering Sciences, 2024)
This paper is about Am-Be neutron source irradiation of InP Quantum Dot Laser diode. A QD LD was irradiated for 24 hours and 48 hours. The laser undergone IV characterization experiments before, after the first and second irradiations. A computer simulation using GAMOS helped in analyzing the given results from IV curves. The results showed an improvement in the QD LD series resistance, current density and overall, ideality factor at all measured temperatures. This is explained by the activation of the QD LD Indium composition to Strontium, ionization of the compound QD LD materials, and by the energy deposited to the QD LD.